Microelectrode glucose biosensor based on nanoporous platinum/graphene oxide nanostructure for rapid glucose detection of tomato and cucumber fruits. (13th January 2022) - Wu, Binfang; Xu, Haitao; Shi, Yufeng; Yao, Zhijie; Yu, Jiayu; Zhou, Hua; Li, Yunpeng; Chen, Qiulan; Long, Yongbing
Abstract: A microelectrode glucose biosensor based on a three-dimensional hybrid nanoporous platinum/graphene oxide nanostructure was developed for rapid glucose detection of tomato and cucumber fruits. The nanostructure was fabricated by a two-step modification method on a microelectrode for loading a larger amount of glucose oxidase. The nanoporous structure was prepared on the surface of the platinum microelectrode by electrochemical etching, and then graphene oxide was deposited on the prepared nanoporous electrode by electrochemical deposition. The nanoporous platinum/graphene oxide nanostructure had the advantage of improving the effective surface area of the electrode and the loading quantity of glucose oxidase. As a result, the biosensor achieved a wide range of 0.1–20.0 mmol/L in glucose detection, which had the ability to accurately detect the glucose content. It was found that the three-dimensional hybrid nanostructure on the electrode surface realized the rapid direct electrochemistry of glucose oxidase. Therefore, the biosensor achieved high glucose detection sensitivity (11.64 μA·L/(mmol·cm 2 ), low detection limit (13 μmol/L) and rapid response time (reaching 95% steady-state response within 3 s), when calibrating in glucose standard solution. In agricultural application, the as-prepared biosensor was employed to detect the glucose concentration of tomato and cucumber samples. The results showed that the relative deviation of this method was less than 5% when compared with that of high-performance liquid chromatography, implying high accuracy of the presented biosensor in glucose detection in plants.